Alterations in Mitochondrial Quality Control in Alzheimer’s Disease - Cai, Qian; Tammineni, Prasad (Frontiers in Cellular Neuroscience, 2016)
Mitochondrial dysfunction is one of the earliest and most prominent features in the brains of Alzheimer’s disease (AD) patients. Recent studies suggest that mitochondrial dysfunction plays a pivotal role in the pathogenesis of AD. Neurons are metabolically active cells, causing them to be particularly dependent on mitochondrial function for survival and maintenance. As highly dynamic organelles, mitochondria are characterized by a balance of fusion and fission, transport, and mitophagy, all of which are essential for maintaining mitochondrial integrity and function. Mitochondrial dynamics and mitophagy can therefore be identified as key pathways in mitochondrial quality control. Tremendous progress has been made in studying changes in these key aspects of mitochondrial biology in the vulnerable neurons of AD brains and mouse models, and the potential underlying mechanisms of such changes. This review highlights recent findings on alterations in the mitochondrial dynamics and mitophagy in AD and discusses how these abnormalities impact mitochondrial quality control and thus contribute to mitochondrial dysfunction in AD.